Fire is a major driver of patterns of genetic diversity in two co-occurring Tasmanian palaeoendemic conifers - Worth, James R. P.; Jordan, Gregory J.; Marthick, James R.; Sakaguchi, Shota; Colhoun, Eric A.; Williamson, Grant J.; Ito, Motomi; Bowman, David M. J. S. (Journal of biogeography, 2017)
Aim: The impacts of Holocene fires on the genetic architecture of fire-intolerant species have largely been overlooked. Here, we investigate the relative impacts of the last glacial climate versus Holocene fires on the genetic diversity of two co-occurring, fire-intolerant conifers using a comparative population genetic study. Location: The palaeoendemic plant-rich montane rain forests and alpine coniferous heath of Tasmania, Australia. Methods: The Tasmanian endemic conifers Athrotaxis cupressoides D. Don (461 samples from 20 populations) and Diselma archeri Hook.f. (576 samples from 23 populations, 16 of which were for sites sampled for A. cupressoides), were genotyped using eight and nine EST nuclear microsatellites respectively. Genetic diversity and structure was compared between the two species and the factors underlying genetic patterns in both species were investigated by examining isolation by distance, correlations with Last Glacial Maximum modelled distributions and the fossil record, and a fire history index of the sampled stands. Results: The range-wide genetic structure of the two species was similar (Fst = 0.09 and F'st = 0.21 for A. cupressoides versus D. archeri; Fst = 0.06 F'st = 0.24), and there were significant correlations between species for population-based expected heterozygosity, allelic richness, private alielic richness and pairwise genetic divergences. Furthermore, genetic diversity metrics decreased significantly with an index of fire history. Given fossil evidence and modelling evidence that both species occurred near their current ranges during the last glaciation and a lack of evidence for isolation by distance in either species, the plausible explanation for the patterns of diversity is genetic decline resulting from repeated Holocene fires. Main conclusions: Our study suggests that fire can have substantial impacts on genetic structure and diversity of plant species, particularly those without fire-tolerant traits, and that any increases in fire resulting from climate change may impose substantial threats to such species. In Tasmania, the observed increase in dry lightning in recent years, combined with periods of abnormally dry conditions, may therefore further degrade the range and genetic diversity of fire-intolerant palaeoendemic species.